Costs of EMU from a regional approach: the Spanish case - Blanca Sanchez-Robles; Jose Villaverde (European Regional Science Association (ERSA), 2001)
In this paper we look at the impact of EMU on Spanish regional disparities in the framework of the Optimal Currency Areas theory and upon its distinction between benefits and costs of a monetary integration. In particular, here we want to deal with the main potential source of costs for the Spanish regions: the likelihood of asymmetric shocks in the economy. In this regard, we try to ascertain the degree of correlation among the business cycles of the Spanish regions, and also with respect to the European and Spanish cycle. The technique employed in the paper ( following Peiro, 2000) focuses on the cross correlations among relevant variables at the regional and the national level such as the behaviour of industrial production or the rate of inflation. We proceed in two steps. First we filter the series in order to get non-autocorrelated residuals. Next we compute the asymptotic distribution of the contemporaneus correlation among the variables in order to know to which extent business cycles behave according to a similar pattern. This method will shed some light on the question about the degree of comovements in the cycles. If the comovements seem to be high - as we expect, based upon other results -, then we may consider than the probability of the Spanish regions suffering asymmetric shocks is less severe.
Keywords: 330